Comparative analysis of Gasifier-CI engine performance and emissions characteristics using diesel with producer gas derived from coal– briquette-coconut shell-mahua feedstock and its blends - Raj R.; Tirkey J.V.; Jena P.; Prajapati L.K. (My University, 2025)
In this study, gasifier-dual fuelled engine (G-DFE) performance was conducted and compared together with gasification of individual feedstock (i.e., mahua wood, coconut shell, sawdust briquette) and their blends with low-grade coal. Additionally, the performance of different sets of feedstock gasification and engine utilization were compared with optimal input and output response using response surface methodology (RSM). The inputs of G-DFE include gasification equivalence ratio (GER) and engine load percentage. The G-DFE performance includes engine brake thermal efficiency (BTE), diesel saving (DS), and CO, CO2, HC, and NOX emissions. Results depict biomass co-gasification blends presented higher engine performance than single feedstock gasification. The (briquette + mahua) producer gas (PG) based dual fuel (DF) engine offers a maximum BTE of 27.6% at input condition of GER 0.12 and 100% load. The maximum DS of 63.44% was obtained for coconut shell G-DFE. Regarding optimum emission, the maximum CO and HC, belong to the setting of GER 0.10 for briquette and (briquette + mahua) G-DFE. The maximum CO2 and NOX belong to the setting of GER 0.10, 100% load for (briquette + mahua), and GER 0.43, 100% load for mahua G-DFE, respectively. Further, the study's experimental results and optimizations can guide G-DFE management for improved operation and reduced environmental footprint. © 2024 Elsevier Ltd